2020
DOI: 10.1002/pssr.202000062
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Perovskite Solar Cells Based on CdSe/ZnS Quantum Dots Electron Transporting Layer with Superior UV Stability

Abstract: Organic-inorganic perovskite materials with their outstanding optoelectronic properties have made a revolution in the field of optoelectronic devices. [1][2][3][4][5][6][7][8] Among all thin film photovoltaics (PVs), perovskite solar cells (PSCs) show a fast progress in a short period of time with high efficiency exceeding 25%, due to their great absorption, long diffusion length, high-quality crystals, low cost, and low-temperature processing. [9][10][11][12][13][14] Over the past years, researchers mostly fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Compared to other CdSe QDs, the green one has a greater band gap, leading to a lower recombination rate in solar cells. Thus, CdSe/ZnS (green) is an potential candidate for enhancing PV performance [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Compared to other CdSe QDs, the green one has a greater band gap, leading to a lower recombination rate in solar cells. Thus, CdSe/ZnS (green) is an potential candidate for enhancing PV performance [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, CdSe/ZnS QDs (PLQE of 85%) with green emission were proposed as ETLs for the first time. [ 118 ] However, it needs a vacuum technique for perovskite film deposition to prevent the solvent to dissolve the underneath QD layer.…”
Section: Strategiesmentioning
confidence: 99%
“…Apart from the efficiency improvement, these QDs have shown improved PSC stability under continuous illumination of light and under UV light. Tavakoli et al [ 160 ] reported the first incorporation of CdSe/ZnS core–shell QDs of green and red emissions as an ETL and DC dual layer. The measured PLQE was 85% for these QDs and showed how efficient it is at converting high‐energy photons to low‐energy photons.…”
Section: Materials For Pscsmentioning
confidence: 99%
“…e) The normalized PCE of TiO 2 and QD (green) devices under UV light. Reproduced with permission [160]. Copyright 2020, Wiley-VCH.…”
mentioning
confidence: 99%